Uyghur and China in The American Media Discourse: A Critical Discourse Analysis of CNN News Articles - Prayudha Prayudha; Ma’ruf Fawwaz (Universitas Ahmad Dahlan, 2019)
This paper analyzes the textual aspects in Critical Discourse Analysis (CDA) Norman Fairclough model of CNN news discourse about Uyghur issue. When this research is conducted, there are only at least five articles specifically discussing Uyghur issue that are 29th December 2011, 29th February 2012, 29th February 2012, 30th October 2013, and 5th September 2014 publications. The research focuses on analyzing the text representation and the relation between participants in the discourse. Objectives of the paper are: 1) to analyze the text representation of news in the news channel of CNN related to the Uyghur case, and 2) to analyze the relation between participants in the news channel of CNN related to the Uyghur case. The subject of this paper is Uyghur issue as reflected in the news articles of CNN International. The paper applies qualitative descriptive method. As a consequence: CNN often put formality features and a vague vocabulary to block and obscure the negative value from the readers to China. The relation here is presented by CNN to China rather than CNN to Uyghur. It is reflected by the power of the status of China.